PENGEMBANGAN E-MODUL TRANSFORMASI GEOMETRI BERBANTUAN PADLET TERKAIT KEMAMPUAN KONEKSI MATEMATIS PESERTA DIDIK SEKOLAH MENENGAH PERTAMA - Septriani, Anisa; Elsa; Khaerunnisa, Najlaa Kania; Sundhari, Rachma; Auliya, Selma (Universitas Islam Nusantara, 2024)
The need for students to use appropriate teaching tools using information technology is a challenge for educators. So it is necessary to develop teaching tools that are assisted by information technology, including e-modules. This study aims to determine the validity and mathematical connection ability of students after using the Padlet-assisted geometry transformation e-module. The research method uses Research and Development (R&D) with ADDIE's design. The data sources came from material expert validators, media experts, and students. The data collection technique uses validation sheets of material experts, media experts, observations, questionnaires, and mathematical connection ability tests. Data on validation, observation, and questionnaire results were analyzed by percentage and descriptive analysis and test result data were analyzed by percentage of learning completeness. Based on the results of the analysis carried out, it can be concluded that the e-module developed is very valid. The average value of mathematical connection ability is 80.28 with moderate criteria.